Impacts of genomic alterations on the efficacy of HER2-targeted antibody–drug conjugates in patients with metastatic breast cancer - Riqing Huang; Anqi Hu; Qixiang Rong; Ditian Shu; Meiting Chen; Wei Yang; Yue Zhang; Qiufan Zheng; Xin An; Cong Xue; Haifeng Li; Yanxia Shi (Journal of Translational Medicine)
Abstract Background HER2-targeted antibody–drug conjugates (ADCs) have revolutionized the treatment landscape of metastatic breast cancer. However, the efficacy of these therapies may be compromised by genomic alterations. Hence, this study aims to identify factors predicting sensitivity to HER2 ADC in metastatic breast cancer. Methods This comprehensive real-world retrospective study collected clinical data from patients diagnosed with metastatic breast cancer and performed genomic profiling using targeted next-generation sequencing. The study analyzed the associations between genomic alterations and clinical outcomes of HER2 ADC treatment. Results Sixty-three patients were included in this study, 33 with HER2-low breast cancer and 30 with HER2-positive breast cancer, respectively. The most frequently altered genes were TP53 (69%), PIK3CA (45%), MYC (35%), and ERBB2 (35%). Patients with amplifications in cell cycle-related genes showed inferior median progression-free survival (PFS) than those without amplifications (2.07 months vs. 8.40 months; HR = 5.24; 95% CI 2.11–13.01; p < 0.001), particularly in HER2-low patients (2.07 months vs. 8.27 months; HR = 4.23; 95% CI 1.50–11.91; p = 0.004). Additionally, ERBB2/CDK12 co-amplification exhibited a superior median PFS in all patients (19.33 months vs. 5.43 months; HR = 0.13; 95% CI 0.04–0.45; p < 0.001) and in HER2-positive patients (19.33 months vs. 6.87 months; HR = 0.18; 95% CI 0.05–0.72; p = 0.007). Multivariate analysis indicated that amplification in cell cycle-related genes was an independent predictor of inferior PFS (HR = 4.46; 95% CI 1.08–18.40; p = 0.039), while the presence of ERBB2/CDK12 co-amplification was independently correlated with superior PFS (HR = 0.16; 95% CI 0.04–0.65; p = 0.010). Conclusions Amplification in cell cycle genes may contribute to primary resistance of HER2 ADC in HER2-low breast cancer. ERBB2/CDK12 co-amplification may be a potential biomarker for favorable responses in HER2-positive breast cancer.